Factors inhibiting sustainable provision of water and sanitation services in Capricorn District Municipality - Mabotha, P. A. P. (The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference, 2020)
Since the inception of the democratic government in 1994, South Africa has enacted policies, which are no longer segregating people in terms of their colour, creed and culture. The newly enacted policies call for clean administration which is not characterised by corrupt activities, maladministration and unskilled personnel. These requirements are not fully adhered to because in most Municipalities, policies are met with practice inconsistencies. Corruption, unskilled staffing and short-lived solutions that hinder government's focus to align with the Sustainable Development Goal's initiatives, delay in achieving the National Development Plan and Medium-Term Strategic Frameworks. The aftermath of maladministration and corruption are seen through increasing unemployment, inequality and poverty even at the local government sphere. Given the democratic dispensation, which has taken place for 26 years, the government is still failing to provide clean water and decent sanitation to all South African citizens. This happens despite several policy directives issued by government such as the White Paper on Water and Sanitation. Lack of training and staff development when transferring water and sanitation functions to municipalities by the former Apartheid National government contributed negatively to water and sanitation delivery. End users of water and sanitation services experience frustration due to lack of technical and administrative capacity. Consequently, these, led to prolonged service delivery crisis. The paper is derived from the review of literature and the conceptual analysis of documents, books, journals and government reviews. Consequently, the paper 's findings revealed that at the operational level there are gaps that need to be filled on unskilled staff as that contributes to corruption / maladministration and short-lived solutions instead of long-term/permanent solutions to problems of water and sanitation. Keywords: Effluent, Sanitation, Water care, Water born infections
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Effluent; Sanitation; Water care; Water born infections; Sanitation -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo